The Effectiveness of Social Assistance Distribution Policy for Extreme Poverty Eradication in Indonesia - Pertiwi, Cita; Oktarina, Adelia; Suprianto, Yakobus; Widjajawati, Erwina; Alkadri, Alkadri; Nababan, Febrina Elia; Rucianawati, Rucianawati; Aziz, Nyimas Latifah Letty; Nadila, Syarfina Mahya; Fitriana, Nur (Journal of Indonesian Economy and Business, 2025)
Introduction/Main Objectives: In order to achieve target 1.1 of the Sustainable Development Goals (SDGs), i.e., to end extreme poverty by 2030, the Indonesian Government encourages the distribution of social assistance as one of the main programs. Background Problems: There are several issues related to the distribution of social assistance that impact the effectiveness of this program. This study aims to investigate the challenges and evaluate possible solutions for the effectiveness of social assistance distribution. Novelty: This study proposes alternative solutions to improve the effectiveness of social assistance distribution in Indonesia. Research Methods: This research uses a descriptive qualitative approach and SOAR analysis (strengths, opportunities, aspirations, and results). The data have been obtained from a literature review and focus group discussions. Finding/Results: The results of the analysis identify three problems, namely (i) inaccuracy of the target beneficiary data, (ii) absence of formed cooperative between stakeholders in the distribution process, and (iii) the amount of cash in the social assistance has not been able to meet the cost of living in several regions in Indonesia. Solutions that can be used to overcome these problems are (1) updating the data and improving the accuracy of targeting of social assistance, (2) strengthening the synergy of the social assistance program organized by government, (3) an adjustment, carried out by local governments, of the value of social assistance benefits, and (4) strengthening the supervision of the social assistance distribution process. Conclusion: The alternative solutions above are "tactical" approaches that need to be employed by the government to increase the effectiveness of social assistance distribution to alleviate extreme poverty.